Fact-checking and financing: Agência Lupa’s projects in the fight against disinformation - Nóbrega, Lizete (2022)
The practice of fact checking is one of the responses that arise in a significant way to the phenomenon of information disorder. Based on this understanding, the present article proposes to identify, through a case study, the strategies of Agência Lupa to guarantee the financing of the fight against disinformation through special projects. Based on the identification and analysis of the initiatives developed throughout 2020, we identified the main potentialities and limits of the practice.